The impact of fear on the effectiveness of customer empowerment-messages in online retailing - A. Selin Atalay; Siham El Kihal; Thilo Pfrang (Psychology & Marketing, 2022)
We explore the effectiveness of empowerment-messages in two contexts of fear caused by an existential threat: COVID-19 pandemic and economic fear. We show in a field experiment that an empowerment-message, which increased sales of an online retailer by 13% before COVID-19 lockdowns when fear was low, does not have the same effect post-COVID-19~lockdowns when fear is high. Three follow-up experiments show that when fear is low, an empowerment-message makes individuals feel responsible and increases purchase. When fear is high, an empowerment-message does not make individuals feel responsible and does not improve purchase. We find that personal control that is generally desired, does not resonate with individuals in the context of fear caused by an existential threat. This implies that marketers should reconsider their use of marketing efforts that empower consumers in high fear contexts.
Keywords: 650; COVID-19; economic fear; empowerment; existential threat; fear; online retailing